THE CHALLENGE FOR DETERMINATION OF GLOBAL FRAUD LOSS – A QUALITATIVE STUDY - Syed Zubair Ahmed (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The high profile fraud incidents have captured the attention of people around the world about the real cost of accounting fraud. The business world is undeniably brimmed with scams and frauds that removed illegitimately billions of dollars. With the increasing number of high-profile scandals, the topic of fraud has attracted unprecedented attention in recent history. The direct losses from fraud and the impact of fraud have grown significantly and simply too costly which conveniently cannot be overlooked. Accordingly, the implications for the global determination of fraud loss has gained ground and has risen to prominence during recent years. The present study aims to examine why it is crucial to measure economic crimes or fraud and how the figure of global fraud loss can be quantifiable. Assessing and identifying the scale of loss from fraud is an important first step toward building a strategy for combating fraud. Equally important to developing a methodology for the accurate measurement of fraud loss globally. This paper explores how a better measurement is critical to a properly designed and strategic response to fraud. Better measurement of global fraud loss can provide a benchmark for exercising anti-fraud strategies, how the programs and activities can work to advantage. How to overcome data quality of global fraud loss and how to ensure the accuracy in exercising the collection methodologies. The methodology applied in this study is a qualitative case study method. The qualitative approach is aimed to determine, define, and investigate research problems. There is no denying the truth that there is no consistent and robust measure across global jurisdictions for determining fraud loss and error. The objective of measuring global fraud and error can be accomplished by implementing and legislating a global standard. The proposed changes are being envisaged as a guide to a global standard to measure the global loss from fraud.